ANALISIS PENETAPAN INSENTIF PELAYANAN TENAGA PERAWAT DI RSUD ARGA MAKMUR KABUPATEN BENGKULU UTARA - Puspita, Oni (Jurnal Governance dan Administrasi Publik, 2017)
Hospital Arga Makmur North Bengkulu District General Hospital is owned by the Government of North Bengkulu is a self-financing unit area rate calculation is based on Unit Cost of health care. Budget Hospital derived from hospital admissions based on Regional Regulation No. 24 Year 2001 on Health Services Levy and North Bengkulu Regent Decree No. 14 of 2002 on Primary Health Service Levy Class A / B and Class I in hospitals Arga Makmur North Bengkulu district . Nurses incentives stipulated in the Decree of the Director of Hospital Arga Makmur Number: 900/0997/RSUD/2013 date October 18, 2013. Unbalance problems occurred and nurses care incentives. This study is a descriptive qualitative study approach through in-depth interviews, bench marks, and focus group discussions (FGD) to provide an overview of the factors that influence the determination of service incentive nurses. Results showed unequal mass acceptance nurses less incentive berazas justice that needs to be improved in the incentive distribution service nurses in hospitals Arga Makmur This study suggests reviewing the Regional Regulation No. 24 of 2001 on Health Services Levy and northern Bengkulu Regent Decree No. 14 of 2002 on Primary Health Service Levy Class A / B and Class I in hospitals Arga Makmur and Decree of the Director of Hospital Arga Makmur No.: 900 / 0997/RSUD/2013 dated October 18,2013